2005
DOI: 10.1021/ol047356q
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Assisted Ring-Closing Metathesis of Chiral Diallylamines:  An Efficient Approach to Enantiopure Pyrrolidine Derivatives

Abstract: Lewis acid assisted ring-closing olefin metathesis (RCM) of chiral diallylamines, using the second generation RCM ruthenium-based catalyst, leads to enantiopure pyrrolidine derivatives in 79−93% yields under very mild conditions. The scope of the olefin metathesis has been expanded.With the development of highly stable and active ruthenium alkylidenes bearing N-heterocyclic carbene ligands, 1 the ringclosing metathesis (RCM) reaction has become an important and powerful approach for the construction of many fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 44 publications
1
73
0
1
Order By: Relevance
“…This work has led to the discovery that metathesis of amine-containing substrates could be performed in the presence of substoichiometric amount of Lewis acid. [29] Results presented in Scheme 34 indicated that cyclized product 88a may nevertheless be obtained in 17-27 % yield in the absence of Lewis acid by treatment with a reactive ruthenium catalyst such as 3 or 4. It would be interesting to explore the same reaction with the allylamine analogue of 87 bearing one or two stronger electron-withdrawing groups such as CF 3 or a ketone with the hope of increasing RCM yields.…”
Section: Ruthenium-catalyzed Metathesis Of Amines A-substituted By Anmentioning
confidence: 99%
See 2 more Smart Citations
“…This work has led to the discovery that metathesis of amine-containing substrates could be performed in the presence of substoichiometric amount of Lewis acid. [29] Results presented in Scheme 34 indicated that cyclized product 88a may nevertheless be obtained in 17-27 % yield in the absence of Lewis acid by treatment with a reactive ruthenium catalyst such as 3 or 4. It would be interesting to explore the same reaction with the allylamine analogue of 87 bearing one or two stronger electron-withdrawing groups such as CF 3 or a ketone with the hope of increasing RCM yields.…”
Section: Ruthenium-catalyzed Metathesis Of Amines A-substituted By Anmentioning
confidence: 99%
“…[25][26][27] These approaches may be incompatible with acid-sensitive substrates and are not always successful. [28,29] Very recently, Xiao and Yu disclosed that RCM of diallylamines using a ruthenium-based catalyst could be performed in the presence of 20 mol % of TiA C H T U N G T R E N N U N G (O-i-Pr) 4 . [29][30][31][32] It is of course too soon to evaluate the benefit of this method but first applications appear to give contrasting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect of TiA C H T U N G T R E N N U N G (OiPr) 4 had been previously found in the Ru-catalyzed RCM of N-alkylsubstituted N-tethered dienes. [27] It was proposed that the Lewis acid suppresses at some stage of the catalytic cycle a deactivating coordination of the amino group to the Ruatom. Thus, one or several intermediates of the catalytic cycle of the RCM reaction of 28 a and 28 b with 19 are perhaps deactivated by an intramolecular coordination [2d, 28] of the sulfoximine group to the Ru atom as exemplary depicted for complex 30.…”
Section: Synthesis Of Sulfoximine-substituted N-tethered Trienesmentioning
confidence: 99%
“…In contrast, the use of a single species to catalyze a tandem process is rare. [3] In our search for novel and efficient Ru-catalyzed reactions, [11] we envisaged the ruthenium alkylidene catalyzed cross-metathesis of w-indolyl alkenes 5 with electron-deficient alkenes 6 as the first step in the tandem reaction leading to polycyclic indoles 7. We propose that the active ruthenium species A (derived from the catalyst precursor) would catalyze not only the CM process, but also an intramolecular hydroarylation owing to its Lewis acidity (Scheme 1).…”
mentioning
confidence: 99%